2011
DOI: 10.3945/ajcn.110.002741
|View full text |Cite
|
Sign up to set email alerts
|

Effects of omega-3 supplementation in combination with diet and exercise on weight loss and body composition

Abstract: Background: In addition to the metabolic and cardiovascular benefits of omega-3 (n23) fatty acids, several studies have suggested an added weight loss-enhancing benefit to this supplement. Objective: The objective was to assess whether supplemental omega-3 fatty acids in conjunction with diet and exercise augment weight loss over a 6-mo period. Design: In a single-institution, placebo-controlled, randomized clinical trial, 128 individuals with a body mass index (in kg/m 2 ) between 26 and 40 were assigned to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(57 citation statements)
references
References 42 publications
5
49
0
3
Order By: Relevance
“…Estos resultados coinciden con los de Defina y cols. (32), quienes observaron que tras la suplementación de 3 g·día -1 de O3 durante 24 semanas junto a un plan de entrenamiento y modificación de dieta en pacientes obesos, no potenció la baja de masa corporal o porcentaje de masa grasa por sobre el grupo control (solo dieta y ejercicio).…”
Section: Efectos De La Suplementación De Omega-3 Y Entrenamiento De Iunclassified
“…Estos resultados coinciden con los de Defina y cols. (32), quienes observaron que tras la suplementación de 3 g·día -1 de O3 durante 24 semanas junto a un plan de entrenamiento y modificación de dieta en pacientes obesos, no potenció la baja de masa corporal o porcentaje de masa grasa por sobre el grupo control (solo dieta y ejercicio).…”
Section: Efectos De La Suplementación De Omega-3 Y Entrenamiento De Iunclassified
“…Some studies found an inverse relationship between n-3 PUFAs on body weight and composition [20,21], but other studies did not find such effects [22,23]. Moreover, despite reports of a significant increase in adiponectin following n-3 supplementation [24,25], in other studies, significant changes have not been observed [26,27,28].…”
Section: Introductionmentioning
confidence: 66%
“…Despite the evidence described above, human trials have not always demonstrate the benefits of EPA and DHA supplementation in the treatment of obesity [106]. The dosage of fatty acid supplementation that could result in bioactivity necessary for obesity treatment is difficult to establish because these compounds are already present in the diet and have been combined in different proportions in each study.…”
Section: N-3 Long-chain Polyunsaturated Fatty Acidsmentioning
confidence: 99%